2019
DOI: 10.7717/peerj.7030
|View full text |Cite
|
Sign up to set email alerts
|

Photoprotection practices, knowledge and sun-related skin damage in Spanish beach handball players

Abstract: Background Outdoor sports are a risk activity for skin cancer, especially if adequate sun protection measures are not used. The aim of this study is to examine the photoprotection habits of outdoor (beach) handball players, and to determine the relation between duration of sports practice, photoprotection behaviour and sun-related damage to the skin. Methods This cross-sectional study is based on a health survey of sun exposure and protecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
23
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(26 citation statements)
references
References 35 publications
3
23
0
Order By: Relevance
“…The failure to examine one’s own skin, or to have this done by a dermatologist, may result in a delayed diagnosis of cancer and possibly a poorer prognosis. This aspect of our study corroborates previous research conducted with young athletes [ 29 , 30 ].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The failure to examine one’s own skin, or to have this done by a dermatologist, may result in a delayed diagnosis of cancer and possibly a poorer prognosis. This aspect of our study corroborates previous research conducted with young athletes [ 29 , 30 ].…”
Section: Discussionsupporting
confidence: 93%
“…It was translated from English into Spanish by a group of experts, by consensus on the content of the items translated, and adapted for use with university students. In addition, the questionnaire was expanded with some further items recommended in the literature and considered relevant for this research [ 29 , 30 , 31 ].…”
Section: Methodsmentioning
confidence: 99%
“…The failure to examine one's own skin, or to have this done by a dermatologist, may result in a delayed diagnosis of cancer and possibly a poorer prognosis. This aspect of our study corroborates previous research conducted with young athletes [26,27].…”
Section: Discussionsupporting
confidence: 93%
“…It was translated from English into Spanish by a group of experts, by consensus on the content of the items translated and adapted for use with university students. In addition, the questionnaire was expanded with some further items recommended in the literature and considered relevant for this research [26][27][28]. Besides the items included in the questionnaire, the following information was obtained for each respondent: sociodemographic variables (age, sex, university subject studied and family history of skin cancer); sun exposure practices (number of hours exposed to the sun, between 10 am and 4 pm, during the week and at weekends); number of sunburn episodes in the last year (defined as pain and redness of the skin lasting more than one day); sun protection measures when exposed to the sun, such as making use of shade, wearing sunglasses, a cap or hat, a long-sleeved t-shirt and long trousers; type of skin (Fitzpatrick phototype) [11]; use of sunscreen cream, its protection factor and rate of reapplication; regular personal skin examination and visits to a dermatologist; diagnosis, if any, of skin cancer; outdoor physical activity (hours per day); during physical activity, use of sunscreen, its protection factor and rate of reapplication.…”
Section: Questionnairementioning
confidence: 99%
“…Many health behaviors are formed and established in this period of life, stressing the importance of interventions promoting health behavior to address children and adolescents as target groups [5]. Especially athletes of outdoor sports are exposed to a high dose of UV radiation [6][7][8][9][10]. Mahé et al [11] found that young outdoor athletes had a significantly higher increase of nevi over 2 years than children who did not exercise outdoors.…”
Section: Introductionmentioning
confidence: 99%